Efficacy of Ultra-Rapid Freezing by Direct Immersion into Liquid Nitrogen for Sperm Cryopreservation and Its Potential for Male Fertility Preservation - Bruce K. Campbell, Feda S. Aljaser; Almajed, Faisal S.; Tomlinson, Mathew J. (International Journal of Innovative Research in Medical Science, 2017)
Sperm cryopreservation is a valuable technology to preserve male’s fertility in many species. The success rates of current cryopreservation techniques remain mediocre and are beset by unexplained inter-individual variation. The study aims to devise and evaluate novel ultra-rapid freezing (URF) protocol to improve sperm cryopreservation utilizing approaches suggested to prevent intra- and extra-cellular ice formation relative to conventional slow controlled rate freezing (CRF) and vapour freezing. Experiments initially focused on optimising the entire protocol by reappraising each constituent part of the process in addition to initial evaluation of sperm URF comparing dry ice to liquid nitrogen (LN2) direct plunging. Results showed that URF is feasible and can provide enhanced post-thaw survival over the CRF (P<0.01 sperm progression; P<0.05 motile sperm yield) using no more than 7.5% glycerol added at ambient conditions, particularly if sperm are first gradient prepared. Although findings indicated no difference in sperm motility and morphology between URF and conventional slow vapour freezing, URF using LN2 plunging resulted in increased sperm DNA integrity preservation (P<0.05). It was concluded that the URF protocol showed promising results and minimises the CPA and osmotic stress exposure period and other associated risks and suggestions to overcome the issue of sterility in LN2 were justified. Thus, sperm URF/vitrification is worthy of further development and optimization of the technique.